Analysis And Control Of Genset Damage Risk In The Facility Department Using The Hazard And Operability Study (Hazop) And Fault Tree Analysis (FTA) Methods - Boas Ginting; Hery Irwan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
A generator set (genset) is an essential supporting facility that ensures the continuity of electrical power supply in manufacturing companies during failures of the main power source. Generator failures may interrupt production activities, increase maintenance costs, and reduce overall operational effectiveness. This study aims to identify potential risks of generator set failures using the Hazard and Operability Study (HAZOP) method, analyze the root causes of failures using Fault Tree Analysis (FTA), and propose appropriate risk control recommendations. The research data were collected through observations, interviews, documentation, and historical maintenance records from the Facility Department. The HAZOP analysis revealed that radiator overheating had the highest Risk Score of 20, categorized as an extreme risk, while battery drop and fuel filter blockage each obtained a Risk Score of 16, categorized as high risk. Furthermore, the FTA results indicated that generator failure was caused by several basic events, including battery drop, fuel filter blockage, radiator overheating, alternator failure, starter motor failure, and oil leakage, with a calculated top event probability of 67.2%. The proposed recommendations include implementing preventive maintenance, conducting routine inspections, replacing components based on service life, and improving generator condition monitoring to enhance equipment reliability and minimize operational failure risks.